2016
DOI: 10.2174/1570180813666160720165057
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Catechols Detection as Biomarkers in Schistosomiasis Induced Cancer and Infertility

Abstract: Urogenital schistosomiasis is a chronic infection caused by the human blood fluke Schistosoma haematobium. Schistosomiasis haematobium is a known risk factor for cancer leading to squamous cell carcinoma of the urinary bladder (SCC). This is a neglected tropical disease endemic in many countries of Africa and the Middle East. Schistosome eggs produce catechol-estrogens. These molecules are metabolized to active quinones that cause alterations in DNA (leading in other contexts to breast or thyroid cancer). Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…putida (along with very few Proteobacteria strains), to utilize extraneous steroids such as estrogen, due to the presence of specialized genes, in particular, tesD [ 47 ]. This is of interest because a recent report indicated the availability of catechol estrogens, steroid-like molecules, in the urinary tract during urogenital schistosomiasis infection [ 16 ]. In the present study, apart from being a dominant genus, the proportions of Pseudomonas and P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…putida (along with very few Proteobacteria strains), to utilize extraneous steroids such as estrogen, due to the presence of specialized genes, in particular, tesD [ 47 ]. This is of interest because a recent report indicated the availability of catechol estrogens, steroid-like molecules, in the urinary tract during urogenital schistosomiasis infection [ 16 ]. In the present study, apart from being a dominant genus, the proportions of Pseudomonas and P .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have highlighted the role of estrogen-related molecules from the parasite in disease progression [ 12 ], based on the discovery that they could be oxidized to form adducts [ 13 ], induce infertility in females [ 14 ], and could probably induce error-prone DNA repair [ 15 ]. Molecules related to estrogen were recently detected in urine samples of persons infected with schistosomiasis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is usually developed after prolonged phase of pre-invasive lesions in the cervix [ 2 ]. Therefore, early identification and treatment at its pre-invasive stage may benefit the clients and decrease the burden of morbidity and mortality resulting from cervical cancer [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular intricacies involved in the development of bladder tumours during urogenital schistosomiasis are not clearly defined, and the tumours are usually preceded by abnormal morphologies or pathologies especially in the bladder. Recent studies on the mechanisms of tumour development in schistosomiasis have highlighted the role of estrogen-related molecules from the parasite, as such molecules were found in many urine samples from infected persons in Angola [ 8 , 9 , 10 ]. Also, it was recently shown that an inflammation-regulatory microbiome could play important roles in the maintenance or development of bladder pathologies during infection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%